2010
DOI: 10.1037/a0020792
|View full text |Cite
|
Sign up to set email alerts
|

Bitter avoidance in guinea pigs (Cavia porcellus) and mice (Mus musculus and Peromyscus leucopus).

Abstract: Rejection of bitter substances is common in many species and may function to protect an animal from ingestion of bitter-tasting toxins. Since many plants are bitter, it has been proposed that high tolerance for bitterness would be adaptive for herbivores. Earlier studies conducted on herbivorous guinea pigs (Cavia porcellus) have been used to support this proposal. We tested guinea pigs with bitter plant secondary metabolites (salicin, caffeine, quinine hydrochloride) and bitter protein hydrolysates (two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It is interesting to note that eight of the critical TAS2R16 residues identified here (I13, V77, R124, N148, L185, M200, W261, S273) are conserved between humans and guinea pigs (which have similar bitter taste sensitivity to salicin) but not in mice, which are indifferent to glucopyranosides but become responsive when expressing human TAS2R16 as a transgene 46 , 47 . This suggests that the ligand specificity of murine TAS2R16 may be significantly different than that of the human receptor.…”
Section: Discussionmentioning
confidence: 90%
“…It is interesting to note that eight of the critical TAS2R16 residues identified here (I13, V77, R124, N148, L185, M200, W261, S273) are conserved between humans and guinea pigs (which have similar bitter taste sensitivity to salicin) but not in mice, which are indifferent to glucopyranosides but become responsive when expressing human TAS2R16 as a transgene 46 , 47 . This suggests that the ligand specificity of murine TAS2R16 may be significantly different than that of the human receptor.…”
Section: Discussionmentioning
confidence: 90%
“…98 Guinea pigs, hamsters, and mice also avoid the taste of caffeine, suggesting that it is bitter (or elicits a negative taste quality) to these species as well. 17,99 Rhesus macaques generalize between quinine and caffeine (i.e., they do not discriminate between the taste of quinine and the taste of caffeine), again demonstrating its similarity to other bitter tastes, at least in primates. 100 In rodents, discrimination between caffeine and other chemicals that taste bitter to humans has not received enough attention.…”
Section: Figmentioning
confidence: 99%
“…However, recent studies have shown that this relationship is more complex. For example, some bitter compounds (salicin and protein hydrolysates) evoked stronger avoidance in herbivores than in omnivores [145, 146]. Thus, bitter taste avoidance is species and stimulus dependent, and the premise that herbivores have a generalized reduced bitter sensitivity is not accurate.…”
Section: Bitter Tastementioning
confidence: 99%